Exploring Non-Digital Gamification in English Education: Insights from a Middle School Study - Simbolon, Tetty Novitasari (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the use of non-digital games in English language learning, an area less explored compared to digital gamification methods. It examines how non-technological games engage both teachers and students in a middle school context in Pontianak, Indonesia. The case study involved 34 middle school students and their teacher at a private school, with data collected through observation and interviews conducted after two weeks. An inductive thematic analysis was used to examine the data. The findings showed notable improvements in students' English proficiency, alongside increased collaboration. However, challenges such as knowledge gaps were observed. The study concludes that non-digital games, when designed to align with learning goals and engage students' interests, can effectively support language acquisition. The research encourages educators to experiment with non-digital gamification techniques and apply differentiated instruction strategies to enhance classroom outcomes.